(untitled) (Synergy, 2014)
Inspired by his work in Bogota, Columbia, Dr Todd considers the relationship between libraries and social justice and explores the role of school libraries in equity of opportunity. He poses thought-provoking questions around what this might look like in a country set to take up the challenge of systemic school library development.